Ethno-mycological study on wild mushrooms of Vulkepani Community Forest, Rupandehi District, Nepal - Aryal, Hari Prasad; Budathoki, U. (Nepalese Journal of Biosciences, 2013)
The samples collected from the study site, represented 13 genera of Basidiomycetes belonging to 7 orders, 12 families and 21 species. The dried specimens are housed in the Tribhuvan University Central Herbarium (TUCH), Kirtipur Kathmandu, Nepal.